O sudoku como ferramenta para desenvolvimento do raciocínio e lógica matemática - Rodrigues, Cleyton Ranis Sancha (Universidade Federal do Tocantins, 2024)
The objective of this work was to investigate the reasoning of the students through the performance in the Sudoku hobby, and to show techniques for its development, thus making the process of solving the hobby more efficient, providing an interest in the hobby and helping them to have a more efficient reasoning. logic in the face of problems encountered in math activities. The approach used was qualitative, as a theoretical foundation by authors such as Godinho (2008), Macedo (2011) and Teles (2018). The responses to the questionnaire applied after a workshop named come play Sudoku with students from the Federal University of Tocantins and the Colégio de Tempo Integral Joana Batista Cordeiro, in Arraias-TO, in which participants were presented with the Sudoku pastime and the rules to observe the logical reasoning and later with the resolution techniques. The same development in solving the higher level pastime, the work investigates that the results obtained with Sudoku pastime demonstrate that it can be used as a tool in the teaching-learning process; moreover, it awakens interest in mathematics, in addition to contributing to students’ attention, concentration and reasoning. It was also observed that students dispersed easily and showed little concentration and reasoning when they were introduced to the pastime without the rules and techniques, but after understanding them, they took a liking and interest in Sudoku, and thus it is expected that it will be a source of support. so that mathematics teachers can use Sudoku in their didactic teaching-learning activities